Chemotherapy with cetuximab in head and neck squamous cell carcinoma: immunological aspects and markers of treatment effectiveness in clinical practice - A. I. Stukan; S. I. Kutukova; E. A. Nefedova; V. A. Porkhanov; V. N. Bodnya; T. Yu. Semiglazova; N. A. Tsygan; V. V. Kudrina; I. I. Aseeva; Yu. Yu. Stefanova; A. A. Kurmanaliev; M. A. Chagiev (Опухоли головы и шеи)
Introduction. Chemotherapy in combination with targeted therapy (CT + TT) using a monoclonal antibody against epidermal growth factor receptor (EGFR) cetuximab and subsequent maintenance targeted therapy (CT + TT/TT) is the leading 1st line therapy of recurrent/metastatic head and neck squamous cell carcinoma to achieve objective response irrespective of programmed cell death-ligand 1 (pD-L1) expression level. However, often in clinical practice patient profile does not match characteristics of patients included in registration studies. Therapy selection is based on massive advancement of the tumor, low performance status of the patient, use of various chemotherapy regimes which often decreases therapy effectiveness. This creates a necessity of identification of clinical markers of effectiveness based on the drug's pharmacodynamics and mechanism of action.Aim. To analyze the effect of clinical characteristics, peripheral blood markers, and systemic inflammation on long-term results of CT + TT/TT with cetuximab in cancer of the mucosa of the head and neck.Materials and methods. The prospective observational study performed at the Oncology Department with a course on thoracic surgery of the Kuban State Medical University, included 52 patients with head and neck squamous cell carcinoma receiving CT + TT/TT between 2020 and 2023. Clinical characteristics and results of peripheral blood tests were retrospectively analyzed, indices of inflammatory reaction prior to treatment and 12-16 weeks after CT + TT/TT with cetuximab were calculated. Statistical analysis was performed using the med Calc ver. 20.218 and IBM SPSS Statistics 22 software.Results. CT + TT/TT with cetuximab significantly increased red blood cell count (RBC), lymphocyte-monocyte ratio (LMR), and decreased systemic inflammatory markers (SIM) (p <0.05) 12-16 weeks after the start of treatment. Statistically significant decrease in progression-free survival for baseline RBC <3.9 x 1012/L (area under the ROC-curve, AUC) = 0.780; 95 % confidence interval (CI) 0.616-0.944; p = 0.0008), RBC ≤3.8 x 1012/L 12-16 weeks after the start of therapy (AUC = 0.748; 95 % CI 0.554-0.941; p = 0.0120) was observed. Survival was negatively affected by LMR >3.27 after 12-16 weeks of therapy (AUC = 0.685; 95 % CI 0.486-0.885; p = 0.0691). median survival of patients after the start of CT + TT/TT with cetuximab was 28 months (95 % CI 17-48), progression-free survival was 8 months (95 % CI 5-36). For RBC count >3.8 x 1012/L 12-16 weeks after the start of therapy, risk of progression decreased by 79 % (hazard ratio 0.21; 95 % CI 0.07-0.62; p = 0.0047). Partial response after 12-16 weeks of CT + TT/TT decreased progression risk more than 4-fold (p <0.05). The model decreasing progression-free survival includes baseline RBC ≤3.9 x 109/L, RBC ≤3.8 x 109/L after 12-16 weeks of CT + TT/TT with cetuximab and absence of partial response per the Response Evaluation Criteria in Solid Tumors 1.1 (RECIST 1.1) (AUC = 0.792; 95 % CI 0.706-0.877; p = 0.0079).Conclusion. for prediction of CT + TT/TT with cetuximab effectiveness in patients with head and neck squamous cell carcinoma, baseline characteristics of the peripheral blood and systemic inflammation can be used. Additionally, correlations between these characteristics 12-16 weeks after the start of therapy and treatment effectiveness were observed. Increased RBC as an anemia marker can be considered an indirect mechanism of EGFR signaling pathway blocking by cetuximab through decreased level of interleukin 6, marker of systemic inflammation, and factor of chronic disease anemias hepcidin. In patients with head and neck squamous cell carcinoma, maximal effectiveness of CT + TT/TT with cetuximab requires not only therapy personalization but also anemia correction.